Ответы и объяснения

2012-12-12T18:37:36+04:00

а) Знаменатель нужно привести к виду \sqrt[n]{a^n}

\frac{5}{\sqrt[3]{4}}=\frac{5}{\sqrt[3]{2^2}}=\frac{5\sqrt[3]2}{\sqrt[3]{2^2}\cdot\sqrt[3]2}=\frac{5\sqrt[3]2}{\sqrt[3]{2^2\cdot2}}=\frac{5\sqrt[3]2}{\sqrt[3]{2^3}}=\frac{5\sqrt[3]2}{2}

б) Знаменатель нужно привести к виду (\sqrt[3]{a}+b)(\sqrt[3]{a^2}-b\sqrt[3]{a}+b^2)

\frac{\sqrt[3]6}{\sqrt[3]6+1}=\frac{\sqrt[3]6(\sqrt[3]{6^2}-\sqrt[3]6+1)}{(\sqrt[3]6+1)(\sqrt[3]{6^2}-\sqrt[3]6+1)}=\frac{\sqrt[3]6\sqrt[3]{6^2}-\sqrt[3]6\sqrt[3]6+\sqrt[3]6}{(\sqrt[3]6)^3+1^3}= \\ \frac{6-\sqrt[3]{6^2}+\sqrt[3]6}{6+1}=\frac{6-\sqrt[3]{6^2}+\sqrt[3]6}{6}=

в) Знаменатель нужно привести к виду (\sqrt[3]{a}-b)(\sqrt[3]{a^2}+b\sqrt[3]{a}+b^2)